2016
DOI: 10.1016/j.slsci.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic correlates of inflammatory complement components in young healthy males

Abstract: A growing body of evidence has delineated the predominant role of humoral mediators of inflammation in linking sleep with immunity. Nonetheless, characterization of the relationship between complement components with inflammatory functions and objective sleep measures has not been performed. In this study we investigated the relationships between objective measures of sleep and complement components with inflammatory functions. Thirty-six healthy male university students (age, 23.94±4.23 years; BMI, 23.44±2.67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The finding that diabetes is associated with greater N3 duration was unexpected. One possible explanation for this finding is also related to inflammation, as some of the studies discussed above also found that greater levels of proinflammatory makers are associated with higher N3 (22; 23). Additionally, if people with diabetes are chronically sleep deprived (as suggested by their lower total sleep time), they may have more N3 and less REM due to the homeostatic regulation of sleep.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The finding that diabetes is associated with greater N3 duration was unexpected. One possible explanation for this finding is also related to inflammation, as some of the studies discussed above also found that greater levels of proinflammatory makers are associated with higher N3 (22; 23). Additionally, if people with diabetes are chronically sleep deprived (as suggested by their lower total sleep time), they may have more N3 and less REM due to the homeostatic regulation of sleep.…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this preprint this version posted March 24, 2023. ; https://doi.org/10.1101/2023.03.23.23287631 doi: medRxiv preprint inflammation (21), and inflammatory markers have been associated with greater REM latency (time between sleep onset and first REM epoch) (22), although the latter study did not observe a significant association between inflammation and REM percentage. Another study examined several inflammatory markers and PSG characteristics and found that greater REM percentage was associated with higher levels of complements but also lower levels of IL-6 and CFI (23), all of which are proinflammatory. Therefore, the association between sleep stages and inflammation, particularly in the setting of diabetes, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep measures have been associated with increased levels of inflammatory complement components. 14,28…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been suggested that higher levels of inflammation are associated with poor sleep quality in healthy individuals. 8,9 Meanwhile, other studies have found that inflammation and oxidative stress are possible contributors to frailty and systemic inflammation is a potential mechanism influencing frailty development. 10 It has been suggested that pre-frail and frail individuals have higher levels of inflammatory markers than those in robust individuals, including C-reactive protein (CRP), interleukin-6 (IL-6), and fibrinogen.…”
Section: Introductionmentioning
confidence: 99%